K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

19 tháng 8 2020

( 15,25 - x ) : 25 = 400

=> 15,25 - x = 10000

=> x = - 9984,75

19 tháng 8 2020

\(\left(15,24-x\right):25=400\)

\(15,24-x=10000\)

\(x=15,24-10000\)

\(x=-998476\)

Vậy x = -998476

Read the descriptions of some things you can see when you travel by road. What is the word for each description? The first letter is already there. There is once space for each other letter in the word.0.      You drive fast here.                                                                                    m _o_  _t_  _o_  _r_  _w_  _a_  _y_ 1.      Go here when you need petrol for your...
Đọc tiếp

Read the descriptions of some things you can see when you travel by road. What is the word for each description? The first letter is already there. There is once space for each other letter in the word.

0.      You drive fast here.                                                                                    m _o_  _t_  _o_  _r_  _w_  _a_  _y_

1.      Go here when you need petrol for your car.                                              g __  __  __  __  __ 

2.      This will take you over a river or another road.                                          b __  __  __   __  __ 

3.      You must show this person your driving licence if he asks for it.              p __  __  __  __   __  __  __  __ 

4.      You can go left, right or straight on at this place where two roads meet.    c __  __  __  __  __  __  __  __  __ 

 

5.      If these are red, the traffic has to wait.                                                       l __  __  __  __  __  

1

0.      You drive fast here.                                                                                    m _o_  _t_  _o_  _r_  _w_  _a_  _y_

1.      Go here when you need petrol for your car.                                              gas station

2.      This will take you over a river or another road.                                          b oat

3.      You must show this person your driving licence if he asks for it.              p olice

4.      You can go left, right or straight on at this place where two roads meet.    c rossroads

5.      If these are red, the traffic has to wait.                                                       l ight trafic

19 tháng 8 2020

20 góc nha bn

19 tháng 8 2020

À mình nhầm

20 tháng 8 2020

Mình không biết vẽ hình trên đây nên bạn thông cảm nhé

Xét tam giác CAN có:  Q là trung điểm  của AC

                                    K là trung điểm của NC

=>QK là đường trung bình của tam giác CAN

=> \(\hept{\begin{cases}QK=\frac{1}{2}AN\\QKsongsongAN\end{cases}}\)(1)

Xét tam giác PBN có:   J là trung điểm của BP

                                     I là trung điểm của NP

=> IJ là đường  trung bình của  tam giác PBN

=>\(\hept{\begin{cases}IJ=\frac{1}{2}BN\\IJsongsongBN\end{cases}}\)(2)

mà AN=BN(N là trung điểm của AB)(3)

=>\(\hept{\begin{cases}QK=IJ\\QKsongsongIJ\end{cases}}\)

       Xét tứ giác IJKQ có:

\(\hept{\begin{cases}QK=IJ\\QKsongsong\:IJ\end{cases}}\)       

=> IJQK là hình bình hành                        

19 tháng 8 2020

Vì A và B là hai góc phụ nhau nên : 

=> A + B = 90

mà A = 3 

=> B = 90 - 3 = 87

19 tháng 8 2020

^A và ^B là hai góc phụ nhau 

=> ^A + ^B = 900

=> ^A = 900 - ^B 

2^A = 3^B (1)

Thế ^A = 900 - ^B vào (1) 

=> (1) <=> 2( 900 - ^B ) = 3^B

           <=> 1800 - 2^B = 3^B

           <=> 1800 = 3^B + 2^B

           <=> 1800 = 5^B

           <=> ^B = 1800/5 = 360

^B = 360 => ^A + 360 = 900

               => ^A = 900 - 360 = 540

Vậy ^A = 540 ; ^B = 360

19 tháng 8 2020

ĐKXĐ : \(\hept{\begin{cases}x\ge0\\x\ne9\end{cases}}\)

\(P=\left(\frac{\sqrt{x}}{\sqrt{x}+3}+\frac{x+9}{9-x}\right):\left(\frac{3\sqrt{x}+1}{x-3\sqrt{x}}-\frac{1}{\sqrt{x}}\right)\)

\(P=\left(\frac{\sqrt{x}}{\sqrt{x}+3}-\frac{x+9}{\left(\sqrt{x}+3\right)\left(\sqrt{x}-3\right)}\right):\left(\frac{3\sqrt{x}+1}{\sqrt{x}\left(\sqrt{x}-3\right)}-\frac{1}{\sqrt{x}}\right)\)

\(P=\left(\frac{\sqrt{x}\left(\sqrt{x}-3\right)-x-9}{\left(\sqrt{x}+3\right)\left(\sqrt{x}-3\right)}\right):\left(\frac{3\sqrt{x}+1-\sqrt{x}+3}{\sqrt{x}\left(\sqrt{x}-3\right)}\right)\)

\(P=\frac{x-3\sqrt{x}-x-9}{x-9}.\frac{x\left(\sqrt{x}-3\right)}{2\sqrt{x}+4}\)

\(P=\frac{-3\left(\sqrt{x}+3\right)}{\left(\sqrt{x}+3\right)\left(\sqrt{x}-3\right)}.\frac{x\left(\sqrt{x}-3\right)}{2\left(\sqrt{x}+2\right)}\)

\(P=\frac{-3x}{2\left(\sqrt{x}+2\right)}\)

20 tháng 8 2020

BẠN NÀO BIẾT TA

19 tháng 8 2020

Bài 1 : 

a) \(P=\left(\frac{1}{x-\sqrt{x}}+\frac{1}{\sqrt{x}-1}\right):\frac{\sqrt{x}}{x-2\sqrt{x}+1}\)

\(P=\left(\frac{1}{\sqrt{x}\left(\sqrt{x}-1\right)}+\frac{1}{\sqrt{x}-1}\right).\frac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}}\)

\(P=\frac{1+\sqrt{x}}{\sqrt{x}\left(\sqrt{x}-1\right)}.\frac{\sqrt{x}-1}{\sqrt{x}}\)

\(P=\frac{\sqrt{x}+1}{x}\)

b) \(P>\frac{1}{2}\)

\(\Leftrightarrow\frac{\sqrt{x}+1}{x}>\frac{1}{2}\)

\(\Leftrightarrow\frac{\sqrt{x}+1}{x}-\frac{1}{2}>0\)

\(\Leftrightarrow\frac{\sqrt{x}+1-2x}{x}>0\)

\(\Leftrightarrow\sqrt{x}-2x+1>0\left(x>0\right)\)

\(\Leftrightarrow\sqrt{x}+x^2-2x+1-x^2>0\)

\(\Leftrightarrow\sqrt{x}+x^2+\left(x-1\right)^2>0\left(\forall x>0\right)\)

Vậy P > 1/2 với mọi x> 0 ; x khác 1

19 tháng 8 2020

Bài 2 : 

a) \(K=\left(\frac{\sqrt{a}}{\sqrt{a}-1}-\frac{1}{a-\sqrt{a}}\right):\left(\frac{1}{\sqrt{a}+a}+\frac{2}{a-1}\right)\)

\(K=\left(\frac{\sqrt{a}}{\sqrt{a}-1}-\frac{1}{\sqrt{a}\left(\sqrt{a}-1\right)}\right):\left(\frac{1}{\sqrt{a}\left(\sqrt{a}+1\right)}+\frac{2}{a-1}\right)\)

\(K=\frac{a-1}{\sqrt{a}\left(\sqrt{a}-1\right)}:\frac{a-1+2\sqrt{a}\left(\sqrt{a}+1\right)}{\sqrt{a}\left(a-1\right)\left(\sqrt{a}+1\right)}\)

\(K=\frac{a-1}{\sqrt{a}\left(\sqrt{a}-1\right)}.\frac{\sqrt{a}\left(a-1\right)\left(\sqrt{a}-1\right)}{a-1+2a+2\sqrt{a}}\)

\(K=\frac{\left(a-1\right)^2}{3a+2\sqrt{a}-1}\)

b) \(a=3+2\sqrt{2}=2+2\sqrt{2}+1=\left(\sqrt{2}+1\right)^2\)( thỏa mãn ĐKXĐ )

Thay a vào biểu thức K , ta có :

\(K=\frac{\left(3+2\sqrt{2}-1\right)^2}{3\left(3+2\sqrt{2}\right)+2\sqrt{\left(\sqrt{2}+1\right)^2}-1}\)

\(K=\frac{\left(2+2\sqrt{2}\right)^2}{9+6\sqrt{2}+2\left|\sqrt{2}+1\right|-1}\)

\(K=\frac{\left(2+2\sqrt{2}\right)^2}{8+6\sqrt{2}+2\sqrt{2}+2}\)

\(K=\frac{\left(2+2\sqrt{2}\right)^2}{10+8\sqrt{2}}\)

19 tháng 8 2020

40×33+36×40+31×40

40×(33+36+31)

40×100

4000

19 tháng 8 2020

4 x 10 x 33 + 2 x 36 x 20 + 5 x 31 x 8

= 40 x 33 + 40 x 36 + 40 x 31

= 40 x (33 + 36 + 31)

= 40 x 100 = 4000